2022
DOI: 10.1073/pnas.2200931119
|View full text |Cite
|
Sign up to set email alerts
|

Brain-wide interactions during hippocampal sharp wave ripples

Abstract: Significance Bidirectional communication between the hippocampus and other brain areas via sharp wave ripples (SPW-Rs) has been hypothesized to play an important role in cognitive functions. However, brain-wide coupling to SPW-Rs has been difficult to study at high temporal and spatial resolution. Here, we show that SPW-Rs coincide with transient brain-wide increase of functional connectivity. The diversity in SPW-R features was related to slower excitability fluctuations in cortical and subcortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 65 publications
4
27
1
1
Order By: Relevance
“…When hippocampal ripples occurred, there was an increased probability of ripples in extrahippocampal MTL regions; a shift in LFP power from lower to higher frequencies in these regions; and an increase in MTL-wide neuronal spiking activity. Related long-range effects of hippocampal ripples have been described in both animals and humans ( 21, 22, 24, 37, 53, 55 ). Through these excitatory effects, hippocampal ripples may play a key role in the formation and retrieval of associative memories by coordinating and combining diverse patterns of neural activity from multiple regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When hippocampal ripples occurred, there was an increased probability of ripples in extrahippocampal MTL regions; a shift in LFP power from lower to higher frequencies in these regions; and an increase in MTL-wide neuronal spiking activity. Related long-range effects of hippocampal ripples have been described in both animals and humans ( 21, 22, 24, 37, 53, 55 ). Through these excitatory effects, hippocampal ripples may play a key role in the formation and retrieval of associative memories by coordinating and combining diverse patterns of neural activity from multiple regions.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of wide-ranging neural changes during hippocampal ripples aligns with previous reports in both animals and humans. In rodents, hippocampal sharp-wave ripples are accompanied by widespread cortical and subcortical activations (22,88,89) and coincide with transient brain-wide increases in functional connectivity (24). In humans, hippocampal ripples are coupled with ripples in many cortical areas (23,33,37) and are accompanied by increased high-frequency broadband activity in widely distributed neocortical sites (40).…”
Section: Neural Changes During Hippocampal Ripplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggested that the hippocampal ripples are coordinated with brain-wide neural dynamics (25,(30)(31)(32). The present study extended these findings by showing that the hippocampal replays are embedded in the global cascade dynamics of sequential activation.…”
Section: Discussionmentioning
confidence: 99%
“…A natural extension for the analyses presented here would be the question of whether such cross-strata co-occurrence manifests in the CA3 and the CA2, which play critical roles in the emergence of ripples (Ylinen et al, 1995;Chrobak and Buzsaki, 1996;Buzsaki, 2015) apart from manifesting theta oscillations (Buzsaki, 2002;Goutagny et al, 2009;Colgin, 2013). Furthermore, although our recordings and analyses were limited to the dorsal hippocampus, it is critical to assess co-occurrences with simultaneous multi-strata recordings along the dorsoventral and proximo-distal axes of the hippocampus involving brain-wide interactions during such events (Nitzan et al, 2022). Importantly, future studies analyses should assess the intracellular counterparts of theta vs. non-theta ripples in the somatic and the dendritic compartments of identified deep vs. superficial neurons.…”
Section: Experimental Designs and Analysis Pipelines Should Explicitl...mentioning
confidence: 99%